KAJIAN YURIDIS PENGGUNAAN REKAM MEDIS UNTUK VERIFIKASI PEMBIAYAAN LAYANAN KESEHATAN - Hary Iskandar; Sabir Alwy; Nurul Hudi (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2018)
The use of patient medical records for hospital payment claims is in essence contrary to the medical records confidentiality rules. This study aims to review the judicial use of medical records in the verification of health care financing in the era of national health insurance. This research uses descriptive study method with normative juridical approach. Qualitative data comes from literature review such as primary, secondary and tertiary law. This study indicates that verifiers with the status of health workers have the legal authority to use patient information in medical records as they relate to the profession. Medical secrets can be opened in the context of quality control and health care costs. Quality control through medical audit, and cost control with health service utilization. This study recommends that verifiers be selected from medical personnel and therefore have the authority to open a medical record.